2014
DOI: 10.3748/wjg.v20.i47.17839
|View full text |Cite
|
Sign up to set email alerts
|

Elevated free cholesterol in a p62 overexpression model of non-alcoholic steatohepatitis

Abstract: AIM:To characterize how insulin-like growth factor 2 (IGF2 ) mRNA binding protein p62/IMP2-2 promotes steatohepatitis in the absence of dietary cholesterol. METHODS:Non-alcoholic steatohepatitis (NASH) was induced in wild-type mice and in mice overexpressing p62 specifically in the liver by feeding the mice a methionine and choline deficient (MCD) diet for either two or four weeks. As a control, animals were fed a methionine and choline supplemented diet. Serum triglycerides, cholesterol, glucose, aspartate am… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
24
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 51 publications
3
24
0
Order By: Relevance
“…Several studies have shown that an MCD diet can eventually induce hepatic fibrosis in WT mice 23,24,29,31,3439 ; however, the time required for mice to develop fibrosis while on an MCD diet varies. In studies by Katsura et al and Simon et al, mice fed an MCD diet for 15 weeks or 2 weeks, respectively, developed fibrosis 35,38 . It is also unclear if longer feeding time on an MCD diet results in more severe fibrosis.…”
Section: Methionine- and Choline-deficient (Mcd) Dietmentioning
confidence: 96%
See 3 more Smart Citations
“…Several studies have shown that an MCD diet can eventually induce hepatic fibrosis in WT mice 23,24,29,31,3439 ; however, the time required for mice to develop fibrosis while on an MCD diet varies. In studies by Katsura et al and Simon et al, mice fed an MCD diet for 15 weeks or 2 weeks, respectively, developed fibrosis 35,38 . It is also unclear if longer feeding time on an MCD diet results in more severe fibrosis.…”
Section: Methionine- and Choline-deficient (Mcd) Dietmentioning
confidence: 96%
“…Several studies have shown that feeding WT mice an MCD diet for as few as 2 weeks and up to 15 weeks resulted in elevated liver enzymes, including aspartate transaminase (AST) and alanine transaminase (ALT) 23,24,31,35,38 . In the study by Itagaki et al WT mice were fed an MCD diet for 30 weeks total and developed increased levels of AST and ALT at only 2 weeks 31 .…”
Section: Methionine- and Choline-deficient (Mcd) Dietmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, mice or rats fed an MCD diet have frequently been used as animal models for NASH as they help clarify the pathogenesis of these disorders and underpin therapies for them [6]. Liver injury induced by an MCD diet is accompanied by elevated transaminases, protein cytokines, oxidative stress and changes in mitochondrial function [7].…”
Section: Introductionmentioning
confidence: 99%